PERANCANGAN BUKU CERITA BERGAMBAR BERWARNA UNTUK ANAK TK STUDI KASUS DI TK HARAPAN MASA - Hardiyanti Prihatiningrum (Pixel :Jurnal Ilmiah Komputer Grafis, 2019)
Current technological developments make many children choose to play with their gadget. This makes them sometimes lazy to read a book. But that can be tricked by story bookspictorial. The picture book itself has several advantages besides drawings that attract children's attention. Like an easy story to understand, contain meaning or stories of life learning, enhance imagination, and the existence of pictures in the story book will give a picture of imagination and fantasy in children. Therefore children are advised to be fond of reading book. Picture books have many variations on the theme the story, like about friendship or other fable stories. And for children who don't like books, can start with this picture book. Can be started by looking at the pictures, then just learning to read contents of the story of the book. In kindergarten HARAPAN MASA itself reading activities the book is still lacking. Most teachers read later students mimic. This is still considered inefficient because not all children will pay attention to. By holding the book reading activity, children are expected TK HOPE MASA can more smoothly read a book In collecting data, the method used by the author is by using interview research methods, surveys, literature studies. For making it using the CorelDRAW X7 program, Adobe Illustrator CS6, Adobe Photoshop CS5 and Manga Studio 5. The existence of this picture book is expected to increase children's interest in reading books.